Reflections on Trevor G. Smith’s "Politicizing Digital Space: Theory, the Internet, and Renewing Democracy" - Rahel Süß (tripleC: Communication, Capitalism & Critique, 2017)
Book review of Trevor G. Smith’s "Politicizing Digital Space: Theory, the Internet, and Renewing Democracy" (2017). University of Westminster Press, ISBN: 978-1-911534-40-